When brands show a human side, hearts open a wide! Enhancing prosocial behavior through anthropomorphized brand messaging in cause related marketing - Durgha Devi, L.; Arumugam, Thangaraja (Frontiers in Communication, 2024)
This paper discusses the influence mechanism of prosocial behavior through anthropomorphized brand messaging in cause related marketing among young adults, based on heuristic systematic model, the study assesses how different modes of information processing shapes consumers’ prosocial behavior, with moderating effect of execution style. An online survey was conducted among 299 young adults in Chennai, Tamil Nadu, India, utilizing a purposive sampling technique. Structural Equation Modeling was applied using Smart-PLS. The findings indicate that anthropomorphized brand message in cause related marketing significantly influence prosocial behavior. Systematic information processing is positively associated with brand anthropomorphism, while heuristic processing shows a negative association. The execution style moderates the relationship between brand anthropomorphism and prosocial behavior, with cause-focused messaging enhancing the effectiveness of anthropomorphism in cause related marketing initiatives. The study suggests that brands can enhance effectiveness of cause related marketing by adopting anthropomorphized messaging, which fosters deeper emotional connectionsand encourages systematic information processing. The implications are significant for marketers aiming to design effective cause related marketing strategies that resonate with socially conscious young adults.